2017
DOI: 10.1002/asi.23814
|View full text |Cite
|
Sign up to set email alerts
|

Scientific evolutionary pathways: Identifying and visualizing relationships for scientific topics

Abstract: Whereas traditional science maps emphasize citation statistics and static relationships, this paper presents a term-based method to identify and visualize the evolutionary pathways of scientific topics in a series of time slices. First, we create a data preprocessing model for accurate term cleaning, consolidating, and clustering. Then we construct a simulated data streaming function and introduce a learning process to train a relationship identification function to adapt to changing environments in real time,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 54 publications
0
68
0
1
Order By: Relevance
“…Only few clinical applications were mentioned, and studies focused on the technological development. The second slice showed that the precursors developed, and some newly generated topics indicating recent ideas and innovations [24]. This slice showed rather a development of matter sciences ("Chemistry" and "Materials sciences, Biomaterials"), than of medical applications [9].…”
Section: Science Mapping With Wos Categories (Figure 2)mentioning
confidence: 99%
See 1 more Smart Citation
“…Only few clinical applications were mentioned, and studies focused on the technological development. The second slice showed that the precursors developed, and some newly generated topics indicating recent ideas and innovations [24]. This slice showed rather a development of matter sciences ("Chemistry" and "Materials sciences, Biomaterials"), than of medical applications [9].…”
Section: Science Mapping With Wos Categories (Figure 2)mentioning
confidence: 99%
“…For studying the science mapping of WoS categories, we set two time slices to trace the evolution of bioprinting topics ( Figure 2) [21,22,24]. The first slice was the beginning of bioprinting, and showed some early-stage topics, such as "Cell & Tissue Engineering" and "Engineering, Biomedical".…”
Section: Science Mapping With Wos Categories (Figure 2)mentioning
confidence: 99%
“…Due to the high volume of data and information available in high-quality scientific databases, bibliometrics and science maps can be used to render data into actionable insights 19,21,[24][25][26][27] . Bibliometrics is defined as statistical techniques and methods to measure of the registered technical and scientific communication 19,21,25 .…”
Section: Bibliometric Analysis and Science Mapsmentioning
confidence: 99%
“…Bibliometrics is defined as statistical techniques and methods to measure of the registered technical and scientific communication 19,21,25 . Science maps are spatial representations of relationships among bibliometric elements -such as authors, institutions, key-words, classifications, disciplines etc 16,18,27 . Science mapping is a hot topic since it has a visual appeal and enables striking interpretations.…”
Section: Bibliometric Analysis and Science Mapsmentioning
confidence: 99%
“…Additionally, we visualize the technological relationships between patent keywords and IPC codes. Visualization is a good way to grasp the associative distribution of technology in patent and technology analysis [27,28]. Leydesdorff and Bornmann (2012) used Google maps to visualize patent data mapping.…”
Section: Introductionmentioning
confidence: 99%